SOSIALISASI KEWIRUSAHAAN DALAM MENINGKATKAN MINAT WIRAUSAHA MASYARAKAT DESA SINDANGSARI - Intan Puspanita (Community Development Journal : Jurnal Pengabdian Masyarakat, 2022)
This community service activity aims to provide socialization related to entrepreneurship so that interest in entrepreneurship in the Sindangsari village community increases, has knowledge related to strategies in entrepreneurship, has strong entrepreneurial spirits, is not easily discouraged, and has creativity and innovation in developing their business. The method of implementing service activities that have been carried out in general is using socialization. The first stage of this activity is to make preparations by surveying the condition of the community in Sindangsari village and determining the location of the socialization activities as well as the targets for the preparation of materials/materials that will be delivered in the socialization activities. The next stage is the stage of implementing the socialization which was carried out in two sessions. In the first session, material was presented on entrepreneurship, the benefits of entrepreneurship, the characteristics of the entrepreneurial spirit, strategies that can be used in developing entrepreneurship and how to increase public awareness and interest in starting entrepreneurship. The second step was a question and answer session and a simulation by providing and showing real examples of various entrepreneurial activities and providing opportunities for participants to practice the socialization materials obtained.